Epidemiological and clinical relationships between diabetes mellitus and periodontal disease - Tin, Myo Han (2015)

(untitled)
Background: Diabetes mellitus (DM) and periodontal disease (PD) are common chronic diseases in medical and oral health practices. DM is in increasing trends in both Malaysia (11.6% in 2006 to 22.6% in 2013) and Myanmar ( 11.8 % in 2003) while prevalence of unhealthy periodontal tissue among community is also high not only in Malaysia (ranged 90.2 % in 2006 to 96.8% in 2010) but also in Myanmar (ranged 77.1% to 98.5% in 2006). Besides, Malaysia-Myanmar comparative study in 2011, seeking treatment for periodontal disease at medical primary care clinics was found out in Malaysia (18%) and Myanmar (44%). In this symposium, epidemiological and clinical relationships between DM and PD will be presented to get awareness on effect of PD on glycemic control of DM patients by primary care physicians for further applications in their practices. Discussion: Bi-directional relationships between DM and PD in terms of epidemiological, clinical link and biological plausibility been published since late 20th century in oral health profession and. PD is recognized as one of modifiable risk factors for DM. Besides, low percent (20-30%) of the patients with glycemic control under medical treatment alone indicates to consider other factors for their glycemic control. The immune response to periodon¬tal bacterial infection of type-2 DM patients does not develop antibodies to pathogens associated with periodontitis. An increasing severity of periodon¬titis has been linked to the development of glucose intolerance, likely because of increased inflammation leading to increase in interleukin-6 (IL-6). Pathological factors in dia¬betes affecting the periodontal tissue are linked to elevated glucose levels in serum with development of advanced glycation end-products (AGEs), altered lipid mechanisms, and oxidative stress, Clinical data have suggested that the presence of AGEs in patients with diabetes is associated with the bio-film on teeth, indicat¬ing an increased risk for periodontal damage. Conclusion: The interrelationship between the periodontitis and diabetes suggests the predisposition of systemic disease to oral infection and vice versa. More awareness of PCPs on the inter-relationship between diabetes mellitus and periodontal disease will improve health care services for DM patients with PD.